2020
DOI: 10.1007/s13258-020-00924-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of simple sequence repeats in Palmae genomes

Abstract: Background Microsatellites or simple sequence repeats (SSRs) have become the most significant DNA marker technology used in genetic research. The availability of complete draft genomes for a number of Palmae species has made it possible to perform genome-wide analysis of SSRs in these species. Palm trees are tropical and subtropical plants with agricultural and economic importance due to the nutritional value of their fruit cultivars. Objective This is the first comprehensive study examining and comparing micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
6
4
1
Order By: Relevance
“…Six classes of perfect SSRs were evaluated (from mono-to hexanucleotide) for their abundance in the assembled genome. Dinucleotides were the most abundant, in accordance with what has been previously reported in literature [30][31][32][33][34][35][36][37][38][39], representing 60.2% of the identified SSRs. Trinucleotides were the second most abundant class (23.7%), followed by tetranucleotides (6.8%).…”
Section: The Ssr Content Of the Poppy Anemone Draft Genomesupporting
confidence: 91%
“…Six classes of perfect SSRs were evaluated (from mono-to hexanucleotide) for their abundance in the assembled genome. Dinucleotides were the most abundant, in accordance with what has been previously reported in literature [30][31][32][33][34][35][36][37][38][39], representing 60.2% of the identified SSRs. Trinucleotides were the second most abundant class (23.7%), followed by tetranucleotides (6.8%).…”
Section: The Ssr Content Of the Poppy Anemone Draft Genomesupporting
confidence: 91%
“…Our findings suggest that in weevils, the number of SSRs is significantly positively correlated with genome size; this is inconsistent with the results reported in [ 35 , 42 ]. Nonetheless, a study reported that the number of SSRs was significantly associated with genome size in 136 insects [ 43 ], which agrees with our results.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is consistent with previous reports that mono- to trinucleotide SSR repeats are more frequent in 23 mosquito species [ 44 ] and six plant species [ 45 ]. Meanwhile, tetra- to hexanucleotide SSRs were the least frequent types in these draft genomes, an observation similar to what has been found in Palmae genomes [ 35 ] and Gossypium species [ 46 ]. More specifically, we observed dinucleotide SSRs to be the most frequent repeat type in R. ferrugineus and I. nitidus , consistent with dicotyledons [ 47 ] and Drosophila [ 14 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Eukaryotic genomes are known to be densely populated with different types of repetitive elements, including tandem repeats [1] and transposable elements (TEs) [2]. TEs were first characterized in plant genomes over 65 years ago by B. McClintock, who discovered genes that move from one chromosome to another and, in so doing, affect the phenotype of the host organism [3,4].…”
Section: Introductionmentioning
confidence: 99%